QUALITY OF PRODUCTS, THE CONCEPT, FUNCTIONS AND FACTORS THAT INFLUENCE IT - Nicoleta- Luminiţa STRÂMBEANU RISTEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present the quality of products, the concept, functions and factors that influence it. Primordial for public health policy and economic policy is to protect the health of organisms, especially humans, at all stages of the technological process. On the worldwide level there is a tendency to ensure that citizens have access to safe and nutritious food, and therefore, it is a must to guarantee the proper functioning of the food industry. International policy protects health at every stage of the production process, that is at every stage of the process, from the agricultural farm up to the consumer. It intends to prevent food contamination and promotes food hygiene and documentation on the health and welfare of plants and animals.